From Peripheral Stereogenic Center to Axial Chirality: Synthesis of 3‐Arylthiophene Atropisomers. Issue 4 (16th November 2022) - Li, Lin; Xi, Junwei; Hong, Biqiong; Gu, Zhenhua
Abstract: A practical synthesis of axially chiral biaryls via chirality transfer from peripheral stereogenic carbon centers is reported. In contrast to the traditional aromatization process of a non‐aromatic structure with ipso stereogenic centers, this method is based on a Pd‐catalyzed carbon‐carbon bond cleavage/ring‐opening reaction of optically active 8 H ‐indenothiophen‐8‐ols with an achiral ligand, enabling synthesis of highly functionalized 3‐arylthiophene atropisomers in high enantioselectivity. Abstract :